Problems of adaptation to conditions of the educational environment for civil and military students - N. L. Denisov (Бюллетень сибирской медицины, 2009)
Factors of adaptation to conditions of the educational environment for civil and military students have been studied. By the end of the education, the number of military students classified to the 1st health group increased by 5% and the number of military students classified to the 3rd health group decreased by 3%. Among civil students, the number of persons classified to the 1st health group decreased by 4%. The state of students’ health is significantly affected by social and psychological factors related to the education, in particular, academic load, disturbed sleep, psychoemotional stresses, relations with teachers. In formation of students’ groups, the emotional component is especially important for undergraduates, while the cognitive and behavioral components are important for graduate students.